iFixit Technical Writing program Overview - Forrest Johnson (2018)
This is a short video introduction for technical writing instructors on the iFixit technical writing program. The video discusses how the program works, what the students produce, and why iFixit runs the program. Relevant to WR227 and other technical writing-adjacent courses.